CURRENT MODE OF TREATMENT OF THE HEPATIC HYDATID CYST - Konstantin Kostov (Peytchinski Publishing, 2022)
Purpose: The aim of the study is to analyze the clinical symptoms, surgical approach and postoperative complications of patients with hydatid cysts of the liver in UMHATEM "N.I.Pirogov". Material and Methods: A total of 39 patients with a diagnosis of hydatid cyst of the liver were admitted to the hospital for a two-year period from 01.01.2019 to 01.01.2021 in the Department of General, Visceral and Emergency Surgery at UMHATEM "Pirogov". Confirmation of diagnosis was based on history, physical examination, laboratory results, ultrasound and CT. Of those hospitalized women were 14 (35.9%), men 25 (64.1%). Results: Тopographically,27 of the cases (69.23%) with liver cysts were located in the right lobe and 12 (30.77%) of them-in the left lobe of the liver. The diameter of the cysts varied from 7 cm-35 cm. There were two groups of patients. With multiple cyst were 29 (74.36%) of the cases, while the group of the single cyst were 10 (25.64%). The operating time varied between 49 and 135 minutes (average 57.4 minutes). The hospital stay ranged from 4 days to 9 days (average 7.1 days). Conclusion: The surgical approach of hydatid liver cyst with the appropriate election of the different therapy opportunities according to the size, number, and location of cysts in the liver, combined with medical therapy, remains the favorable solution.